Modeling of field emission from laser etched porous silicon - Hamid Reza Dehghanpour (Kuwait Journal of Science)
In many modern sciences, electron transfer is required, such as electron microscopes, microwaves, and screens. There have been numerous reports of the formation of microstructures on silicon surfaces using lasers in halogen-containing media and their optical, electrical and other physical properties. A silicon microstructured field emitter is modeled with Fowler-Nortium field diffusion theory, and the breakdown currents are consistent. Breakdown voltage, field gain coefficient, current and current density, and emitter region (in case of breakdown) are considered in the simulation. Comparison between simulation and experimental results shows that the microstructure has field emitter properties and can be used as a new field emitter.